Analisis Puasa Praanestesi dengan Kejadian Haus Praanestesi - Ahmad Mustopa; Fikri Mourly Wahyudi; Eryan Nur Saputra; Fahmi Fabian; Fikri Surya Pratama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to analyze the relationship between fasting duration, type of anesthesia, and surgical duration with the incidence of thirst in pre-anesthetic patients at Welas Asih Regional General Hospital, West Java Province. The method used was an observational analytic approach with a cross-sectional approach. The results showed that the majority of respondents were female (58.8%), with the highest fasting duration being 6–8 hours (64.7%), mild thirst intensity (54.1%), and no signs of dehydration (81.2%). Statistical tests showed a significant association between fasting duration (p=0.018; OR=2.45) and surgical duration (p=0.043; OR=1.97) with thirst intensity. While the type of anesthesia had no effect (p=0.214). In conclusion, fasting duration and surgical duration influence the intensity of thirst in pre-anesthetic patients, while the type of anesthesia has no effect. Keywords: General Anesthesia, Surgical Duration, Pre-anesthetic Fasting, Thirst